2017
DOI: 10.1186/s12882-017-0750-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperchloremia on acute kidney injury in critically ill septic patients: a retrospective cohort study

Abstract: BackgroundHyperchloremia is common in critically ill septic patients. The impact of hyperchloremia on the incidence of acute kidney injury (AKI) is not well studied. We investigated the association between hyperchloremia and AKI within the first 72 h of intensive care unit (ICU) admission.Methods6490 ICU adult patients admitted with severe sepsis or septic shock were screened for eligibility. Exclusion criteria included: AKI on admission, baseline estimated glomerular filtration rate (eGFR) <15 ml/min/1.73 m2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 26 publications
4
23
2
Order By: Relevance
“…In this retrospective review of 7991 patients, we found that exposure to hyperchloremia was not an independent risk factor for postoperative AKI in patients admitted to the ICU after surgery. This result is consistent with the findings of Yessayan et al [ 15 ], who also observed no significant association between hyperchloremia and AKI within 72 h of ICU admission in patients with sepsis or septic shock. However, while Yessayan et al excluded patients with CKD stage 5 [ 15 ], we did not exclude such patients from our analysis.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this retrospective review of 7991 patients, we found that exposure to hyperchloremia was not an independent risk factor for postoperative AKI in patients admitted to the ICU after surgery. This result is consistent with the findings of Yessayan et al [ 15 ], who also observed no significant association between hyperchloremia and AKI within 72 h of ICU admission in patients with sepsis or septic shock. However, while Yessayan et al excluded patients with CKD stage 5 [ 15 ], we did not exclude such patients from our analysis.…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with the findings of Yessayan et al [ 15 ], who also observed no significant association between hyperchloremia and AKI within 72 h of ICU admission in patients with sepsis or septic shock. However, while Yessayan et al excluded patients with CKD stage 5 [ 15 ], we did not exclude such patients from our analysis. However, we excluded 195 patients who died within 72 h after surgery, whereas Yessayan et al included such patients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The finding that hyperchloremic acidosis was associated with worse outcome is also notable because this form of acidosis is not clearly as hazardous from a clinical perspective [ 20 ] although animal studies have shown deleterious effect of hyperchloremia in experimental sepsis [ 21 , 22 ] and in agreement of this recent studies in human reported similar findings. [ 18 , 23 25 ]…”
Section: Discussionmentioning
confidence: 99%